Integrating gender and social inclusion dimensions in climate smart interventions: Experiences from Kenya cluster, AICCRA - Bullock, Renee (2022)
The overall objective of the cluster is to scale socially inclusive climate smart agricultural (CSA) technologies and climate information services (CIS) in drylands with an especial focus on women and youth, which is defined in Kenya as those between the ages of 18-34. An intersectional approach is used as much as possible to understand power relations and social factors that shape scaling of CSA and CIS practices, which may be gender and/or age- based, but may also include other factors, such as ethnicity or wealth, etc. Approaches are primarily gender responsive. Efforts are made to work with women and youth where they have demonstrated agency and to strengthen existing platforms, such as working with and supporting the networks in which women lead or participate or where they have control in value chains. Certain activities, however, require a transformative approach, such as Participatory Rangeland Management interventions, that engage women in rangeland management committees, whereas traditional rangelands institutions have, by and large, excluded women. Strategic engagement can generate changes beyond management institutions, into communities and households.